2006
DOI: 10.1016/j.ygeno.2005.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Genome analysis of Escherichia coli promoter sequences evidences that DNA static curvature plays a more important role in gene transcription than has previously been anticipated

Abstract: We have performed a computer analysis to study the prevalence of DNA static curvature in the regulatory regions of Escherichia coli, detecting a large number of operons with curved DNA fragments in their 5' upstream regions. A statistical analysis reveals that all the global transcription factors identified so far in E. coli have a tendency to regulate operons with curved DNA sequences in their upstream regions. In addition to these global regulators, we also found that the PurR, ArgR, FruR, TyrR, and CytR spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 40 publications
2
37
0
Order By: Relevance
“…We then used this mutated DNA as substrate for a second PCR-mediated mutagenesis to introduce the required changes, different from the wildtype sequence, which would restore the original extent of DNA curvature (pRO310-re) ( Table 1). The effects of these mutations on DNA bending were evaluated by the PCR amplification of these regions (Fb-wt, Fb-mt and Fb-re) and their corresponding analysis by PAGE at 4 u C (Falconi et al, 1993; Flores-Valdez et al, 2003;Olivares-Zavaleta et al, 2006). The mutations had the expected effect on the electrophoretic migration as predicted in silico (Fig.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…We then used this mutated DNA as substrate for a second PCR-mediated mutagenesis to introduce the required changes, different from the wildtype sequence, which would restore the original extent of DNA curvature (pRO310-re) ( Table 1). The effects of these mutations on DNA bending were evaluated by the PCR amplification of these regions (Fb-wt, Fb-mt and Fb-re) and their corresponding analysis by PAGE at 4 u C (Falconi et al, 1993; Flores-Valdez et al, 2003;Olivares-Zavaleta et al, 2006). The mutations had the expected effect on the electrophoretic migration as predicted in silico (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…MUTACURVE (Olivares-Zavaleta et al, 2006), a software developed to determine the topographic profile of a particular DNA region in silico, was used to further define regions with the highest degree of curvature; one of them was found between 2151 and 2135 bp upstream of the P1 transcriptional start point (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…H-NS is necessary for the nucleoid packaging of the bacterial chromosome and regulates a variety of genes depending on temperature (Atlung & Ingmer, 1997;Ghosh et al, 2006;Müller et al, 2006). Gene silencing mediated by H-NS is caused by preferentially binding to AT-rich DNA sequences displaying intrinsic curvatures (Olivares-Zavaleta et al, 2006;Rimsky, 2004;Schröder & Wagner, 2002). Acti-vation of inv in enteropathogenic Yersinia spp.…”
Section: Rova and H-ns Interact Preferentially With Is1667-sequences mentioning
confidence: 99%
“…Nonetheless, it also been demonstrated that primary DNA sequence is not the only source of information in the genome for the transcription regulatory process (Olivares-Zavaleta et al, 2006). According to many authors (e.g, Kanhere & Bansal, 2005a;Klaiman et al, 2009;Wang & Benham, 2006), not only regulatory sequences contain specific sequence elements that serve as target for interacting proteins, but also present different properties, such as: suitable geometrical arrangement of DNA (curvature), propensity to adopt a deformed conformation facilitating the protein binding (flexibility) and physical properties (e.g., stacking energy, stability, stress-induced duplex destabilization).…”
Section: Structural Properties Of Promoter Sequencesmentioning
confidence: 99%